การวิเคราะห์ตัวแปรจำแนกกลุ่มผู้ป่วยจิตเภทที่ป่วยซ้ำและไม่ป่วยซ้ำ - เพชรี คันธสายบัว (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The purpose of this study was to determine variables, which were able to discriminate the groups of relapse and non-relapse schizophrenic patients. Research subjects, selected by clustered sampling, were schizophrenic patients treated in the mental health hospitals under the jurisdiction of Division of Mental Health. Subjects were divided into two groups, 110 relapse and 110 non-relapse schizophrenic patients. Research instruments were the interviewing questionnaires which were developed by the researcher to measure self-care behaviors, health belief, drug compliance behaviors, family relationship, and family expressed emotion. These instruments were tested for the content validity by a panel of experts. Their reliability were .94, .83, .75, .84 and .84, respectively. Gathered data were analyzed by using percentage, mean, standard deviation and discriminant analysis. Major findings were as follows: The variables that could significantly discriminated the groups of relapse and non-relapse schizophrenic patients, at the .05 level, were 5 variables. They were selfcare behaviors in the aspect of preparation for coping with problems, drug compliance behaviors, marital status, family expressed emotion, and health belief in the aspect of perceived benefit of the practice to prevent relapse. That is, in the non-relapse group, schizophrenic patients possessed higher level of the preparation for coping with problems which is one aspect of self-care behaviors, higher level of drug compliance behaviors, and lower level of family expressed emotion than those in the relapse group. In addition, in the non-relapse group, there were more patients who were single or didn’t stay with spouses than in the relapse group. Moreover, patients in the non-relapse group had a higher score of health belief in the aspect of perceived benefit of the practice to prevent relapse than that of the relapse group.